Administrative Preparation for Independent Learning at MAN 2 Palembang - Nabila, Salsa; Zainuri, Ahmad (El-Idare: Journal of Islamic Education Management, 2024)
This study aims to identify and analyze the preparation of learning administration at MAN 2 Palembang, as well as to assess the school's readiness in implementing the Merdeka Belajar concept. The method used is qualitative research with a descriptive approach. Data collection was carried out through observation, interviews, and documentation, with the Vice Principal for Curriculum as the main informant. Data analysis involved data reduction, data presentation, and conclusion drawing. The results of the study indicate that MAN 2 Palembang has taken strategic steps in preparing learning administration, including the development of learning materials aligned with the principles of Merdeka Belajar, flexible scheduling, and training for teachers and administrative staff. The school also strives to integrate technology into the learning process and adjust the curriculum to be more competency-based. However, several challenges have been identified, such as the lack of in-depth understanding of the Merdeka Belajar concept among staff and teachers, limited technological facilities, and unclear regulatory challenges. Human resource limitations and external support also pose obstacles to the optimal implementation of this policy. Overall, despite the challenges, MAN 2 Palembang has shown a strong commitment to preparing learning administration in line with the Merdeka Belajar concept.